PENINGKATAN HASIL BELAJAR JARING-JARING KUBUS DAN BALOK MENGGUNAKAN STRATEGI PEMBELAJARAN INKUIRI DI SEKOLAH DASAR - Harfiningsih, Emi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is backgrounded by the low of student learning result. The purpose of this study was to describe the increase learning mesh work cube and block using inquiry learning strategies for class IV students.This type of research is Class Action Research (CAR). The approach used is a qualitative and quantitative approach. The subjects of the research are teacher and class IV students as much as 36 people. The results of research to point out the inquiry learning strategies can improve the result of learning mesh work cube and block for class IV students. Kata Kunci: peningkatan hasil belajar; strategi pembelajaran inkuiri